STUDY OF GASIFICATION OF BERAU COAL, EAST KALIMANTAN WITH FLUIDIZED BED GASIFICATION - SEPTIANSYAH (NIM 22106327); Pembimbing: Prof. Dr. Ir. Arief Sudarsono, MSc., IKHSAN
Gasification is a process to convert solid fuel like coal into gas fuel consisting of CO, H2, CH4, and N2. Gasification technology has being developed recently because of a rapid increase in oil price. The utilization of coal by gasification technology is expected to be a promising energy alternative in substituting of oil in the future. In this research, coal from Berau, East Kalimantan was used in gasification experiment conducted with fluidized bed system. The advantage of this system is that the experiment could be conducted at moderate temperature and pressure respectively. Variables of the gasification experiment were coal size fraction, coal type (Lati and Tanah Kuning coals), and Air/Coal Ratio. From the experiment conducted in this research, some results such as temperature profile of the process in the gasification column, gas content resulted from the gasification process, net heating value (NHV) of gas resulted from the gasification process, and cold gas efficiency can be reported. The composition of producer gas resulted from gasification process was comprised of 4-17% of CO, 2-8% of H2, and 0.4-2% of CH4 whilst carbon conversion and cold gas efficiency resulted from the experiment were 32-94% and 9-33.5% respectively. Mathematical model in calculating the carbon conversion from experimental variables used in the experiment was also made. With a higher Air/Coal Ratio in the gasification process, it was resulted in higher carbon conversion and cold gas efficiency respectively. This result was produced because of the more air entered into the column, the more gasification reaction occurred. In term of the effect of coal size fraction, it was found that at a relatively same operated temperature, i.e between 400-750oC, the bigger the coal size, the higher the producer gas calorific value. The producer gas from Lati coal had a higher calorific value than the Tanah Kuning coal. In term of gas volume produced during the gasification process, it was found that the higher gas volume produced was not always followed by higher NHV of the producer gas. This condition was found because of the NHV was depending on the amount of CO, CH4, and H2 gasses. In average, for 1 kilogram of coal it could be produced producer gas of 1.5-3 m3.